Mental Health and Psychological Practice in the United Arab Emirates - Al-Karam, Carrie York.; Haque, Amber; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
Mental Health and Psychological Practice in the United Arab Emirates provides a broad overview the practice of psychology in the UAE. Topics covered span the profession from research to clinical practice to the place of Islam within the broader context of psychology.
Keywords: Education; Ethnology -- Middle East; International education; Comparative education; Education; International and Comparative Education; Middle Eastern Culture; Electronic books